(untitled) (Journal of Maize Research and Development, 2016)
The purpose of this study was to assess the socioeconomic condition of maize seed and non-seed producers. A field survey was carried out in sixty households of Khanchikot VDC of Arghakhanchi district during May, 2014. The district was major seed producing district and Khanchikot was found better in seed production than other VDC in district. Simple random sampling technique was used to collect data using pre-tested interview schedule. About 57% were seed producer among the sample. The average family size of household was 5. Dependency ratio was less in seed producing households (0.41) than non-seed producers (0.72). Farmers were involved in the production of certified seed and the major (50%) source of foundation seed was National Maize Research Program, Rampur, Chitwan. The external input like chemical fertilizer was used in fewer amounts in the study area. The seed test was done at regional laboratory, Bhairahawa and sold to DADO, Arghakhanchi. Decision on loan taking, business operation and bank account were taken by males whereas cropping pattern, deficit labor use, religious and social works related decision were taken by females in the household. Major problem in maize production were lack of technical assistance followed by inadequate irrigation facilities. Proper training, extension service and government support on inputs would help in better socio-economic condition and production of maize.